ANALISIS PENILAIAN KINERJA PELAYANAN PUBLIK STUDI KASUS KANTOR CAMAT SAKO KOTA PALEMBANG TAHUN 2018 (BERDASARKAN PEDOMAN PERMENPAN NO.7 TAHUN 2010) - Fikri, Maiza; Irianto, Achmadi (Jurnal Ilmiah Bina Manajemen, 2018)
Maiza Fikri; Achmadi irianto: "Analysis of Public Service Performance Assessment Case Study at Head Office Sako Palembang Year 2018". This study is a study that refers to Perpemman No. 7 of 2010 which is the Public Service Performance Assessment Guidelines which in the last 4 Component Ratings. Methods This study used a qualitative descriptive study design with Mechanical Sampling Sampling is incidental to the year 2015. The results of this study showed that the Performance Assessment granted by the Public Service District Office Sako Palembang is the value of 50, which is perceived performance given Public Service Head Office Sako Palembang ie Most have been met and to explain the document. The conclusion from this study that the District Office as one of the government agencies that provide services to the community felt still less vibrant and well disegi need improvement of service quality to the satisfaction of the community as recipients of services and administrative documents as public agencies that provide services to the community